Implementasi Sistem Informasi Pelayanan Jasa Laundry Berbasis Web pada Track Laundry - Arkanda, Rizal Naufal Farras; Fithri, Diana Laily (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The current development of Information Technology, especially in Indonesia, has developed rapidly. However, behind the progress of information technology which has now developed rapidly, until now most laundries do not have their own information system and still use manual systems, these laundries also do not have a website for their business, consumers will find it difficult to find information related to business profiles, service system, production systems, and types of services offered in laundry businesses. Track Laundry is a web-based application specifically designed to facilitate online laundry services by utilizing the website as part of the production, marketing and operational systems in a laundry business. Utilizing web-based information system design in laundry businesses can make it easier for customers to order services. The method used in this research is to use a waterfall model. This waterfall model provides a sequential software life flow approach starting from analysis, design, coding, testing and support stages. Built using Laravel 10, this application offers various advanced features that support laundry business operations efficiently and effectively. With Track Laundry, customers can easily order laundry services through a user-friendly interface. The ordering process is done quickly with just a few clicks, starting from selecting the type of service, pick-up and delivery schedule, to secure payment.